Coronavirus Impact On Online Purchases Behavior in Japan - Abdullah, Alias; Azhari, Mohd Sharizal; Mohamad Yusoff, Aimi Aqilah (WILAYAH: The International Journal of East Asian Studies, 2021)
The COVID-19 outbreak has impacted almost every aspect of people’s lives in Japan. With the ageing society that more vulnerable to the disease that needs most people to stay home, the Japanese have been adapting to both the outbreak and the regulations. The declaration of a state of emergency since April makes the businesses and stores deemed non-essential to limit their operations. To limit places where people could gather, all schools, institutes of higher learning, and houses of worship were ordered to be closed during the period. Japanese have been spending more time online and have shown more willingness to purchase items online now. Changes in behavior such as needing to work from home or exploring new hobbies while staying at home also present new opportunities for eCommerce. COVID-19 is having a catastrophic impact on many non-essential products in Japan. With the environment being so different to pre-COVID time, COVID-19 has impacted the Japanese eCommerce industry in some ways. COVID-19 pandemic creates a new environment for the Japanese shopping and spending behavior that needs to be discussed further.